Effects of Self-Confidence and Diction on Speaking Skills in Junior High School Students - Mardiana, Mardiana; Laksmana, Boy; Sukardi, Sukardi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research investigates the impact of self-confidence and diction on speaking skills among state junior high school students in Kepulauan Seribu, Jakarta. Utilizing a sample of 86 students from SMPN 133 Pulau Pramuka, SMPN 241 Pulau Tidung, and SMPN 260 Pulau Untung Jawa, the study employed dialogue assessments, questionnaires, and diction tests. The results demonstrate a significant influence of both self-confidence and diction on speaking proficiency. Specifically, self-confidence accounts for 11.54% of the variance in speaking skills, while diction contributes 18.59%. The combined effect of these factors explains 30.1% of the variance in students' speaking abilities. The findings highlight that students with higher self-confidence and better diction exhibit improved speaking skills. These results suggest that educational strategies aimed at enhancing self-confidence and diction can effectively improve students' communication skills. The study underscores the importance of integrating self-confidence and diction development into language education to enhance overall speaking proficiency